2010
DOI: 10.4049/jimmunol.0901719
|View full text |Cite
|
Sign up to set email alerts
|

CD22 Expression Mediates the Regulatory Functions of Peritoneal B-1a Cells during the Remission Phase of Contact Hypersensitivity Reactions

Abstract: While contact hypersensitivity (CHS) has been considered a prototype of T cell-mediated immune reactions, recently a significant contribution of regulatory B cell subsets in the suppression of CHS has been demonstrated. CD22, one of the Siglecs, is a B cell-specific molecule that negatively regulates B cell receptor signaling. To clarify the roles of B cells in CHS, CHS in CD22-/- mice was investigated. CD22-/- mice showed delayed recovery from CHS reactions compared with wild type mice. Transfer of wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 51 publications
2
33
1
1
Order By: Relevance
“…Our findings are consistent with the non-redundant role of B cells and/or B cell-derived IL-10 in limiting skin inflammation in human psoriasis (16-18) and mouse models of cutaneous hypersensitivity and psoriasis-like inflammation (12, 34, 50). Importantly, human psoriasis is associated with low levels of cutaneous IL-10 and clinically responsive to treatment with dermal IL-10 (51), stressing the importance of cutaneously produced IL-10 in limiting skin inflammation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are consistent with the non-redundant role of B cells and/or B cell-derived IL-10 in limiting skin inflammation in human psoriasis (16-18) and mouse models of cutaneous hypersensitivity and psoriasis-like inflammation (12, 34, 50). Importantly, human psoriasis is associated with low levels of cutaneous IL-10 and clinically responsive to treatment with dermal IL-10 (51), stressing the importance of cutaneously produced IL-10 in limiting skin inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…IL-10 + peritoneal B1 cells suppress skin inflammation (12) and we found IL-10 producing B1-phenotype cells in human and mouse skin (Figs. 2B-D and 3E and F).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…1 B1a cells 47 played suppressive roles during the late remission phase. In both situations, Bregs exerted their regulatory roles in an IL-10-dependent manner, and specifically, the identification of CD1d hi CD5…”
Section: Innate Bregs and Autoimmunitymentioning
confidence: 99%
“…Other organ-specific autoimmune disease models, especially EAE [17,18,32,33] and colitis [19,34], have also provided important mechanisms for how The role of B-1 cells in CHS is still controversial, however. While our study, as described above [35], suggests that B-1 cells have a protective role, Tsuji and colleagues demonstrate a promoting, rather than inhibitory, role for peritoneal B-1 cells in CHS [36]. Using Btk-defective xid mice on a CBA background, they demonstrated that Ag-specific IgM Abs from peritoneal B-1 cells are required for the recruitment of effector T cells in the early elicitation phase [36].…”
Section: Regulatory B Cells In Disease Statesmentioning
confidence: 55%